The influence of fuels treatment and landscape arrangement on simulated fire behavior, Southern Cascade range, California - Schmidt, David A.; Taylor, Alan H.; Skinner, Carl N. (Forest ecology and management, 2008)
Wildfire behavior can be modified by altering the quantity, structure, and arrangement of fuel (flammable vegetation) by silvicultural treatments such as forest thinning and prescribed burning. The type and arrangement (including landscape location) of treated areas have been demonstrated to influence wildfire behavior. This study analyzes the response of several key fire behavior variables to variation in the type, amount, and spatial arrangement of fuel treatments for simulated wildfires in mixed-conifer forests of the southern Cascades in the Goosenest Adaptive Management Area (GAMA). NEXUS and BehavePlus were used to simulate pre- and post-treatment stand-level fire behavior. Fire area simulator (FARSITE) was used to simulate landscape-level wildfire behavior in both untreated and treated forest landscapes. In the forest landscape, treatment areas were placed in the landscape according to two strategically designed arrangements and one random treatment arrangement. Treatments included thinning by prescribed burning (burn-only), mechanical thinning (mechanical-only), mechanical thinning followed by burning (mechanical-burn), and no treatment (control). At the stand level, the mechanical-burn treatment most effectively reduced both surface fire (e.g., decreased flame length) and crown fire behavior (e.g., torching index). At the landscape level, treatment type, amount, and arrangement had important effects on both fire spread and fire intensity. In this landscape the most effective treatment arrangement was Finney's optimal SPLATs design. This study shows that there is potential to efficiently reduce high-intensity fire behavior while treating less area by relying on strategically placed treatments.